Individual Preventive Behaviors of COVID-19 and Associated Psychological Factors Among Chinese Older Adults: A Cross-Sectional Online Survey - Duan, Yanping; Hu, Chun; Lin, Zhihua; Liang, Wei; Shang, Borui; Baker, Julien Steven; He, Jiali; Wang, Yanping (Frontiers in Psychology, 2022)
Purpose: Older adults aged 60 years and above are classified as being of high-risk for infection during the COVID-19 pandemic. This study aimed to investigate the associations of psychological factors (motivational factors: risk perception, health knowledge, attitude, subjective norm, motivational self-efficacy, intention; volitional factors: volitional self-efficacy, planning, action control) of preventive behaviors with three preventive behaviors (hand washing, facemask wearing and social distancing) among Chinese older adults during the COVID-19 pandemic. Methods: A cross-sectional questionnaire survey was administered via SOJUMP, a widely used online survey platform in China. 928 older adults (mean=67.24 years, age range: 60-90 years, SD=6.43, 55.9% females) were recruited using a snowball sampling approach from Hubei Province (n=667) and outside Hubei Province (n=261) in China during May 18, 2020 to June 7, 2020. Multiple hierarchical regressions were conducted with four models to examine the association between demographic, past behavior, psychological factors and each preventive behavior. Principal findings: All three preventive behaviors in older adults increased dramatically during the pandemic of COVID-19. Gender, living status, educational level, past behavior, health knowledge, intention and planning significantly predicted hand washing behavior, R2=0.395, F (10, 927) =54.372, p < .001. Gender, education level, important others (e.g., family members or friends) infection, past behavior, health knowledge, planning and action control significantly predicted mask wearing behavior, R2=0.202, F (10, 927) =23.197, p < .001. Living place, past behavior and health knowledge significantly predicted social distancing behavior, R2=0.204, F (9, 927) =26.201, p < .001. Major conclusions: Past behavior and health knowledge predicted all three preventive behaviors. Planning was an important psychological factor for both hand washing and mask wearing behaviors. All those critical demographic and psychological factors are critical for future interventions to facilitate older adults to comply with three preventive behaviors in daily life and to stay healthy during the COVID-19 pandemic.